2016
DOI: 10.19177/jrd.v3e42015722-729
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal status among tibetan refugees residing in jodhpur city

Abstract: Periodontal)status.)Tibetan.)Community)periodontal)index.) Loss)of)attachment.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…According to the World Health Organization (WHO), oral disease burdens are one of the leading health problems that refugees experience [ 17 ]. Among refugees, there is a high prevalence of major oral diseases such as dental caries, periodontal disease, malocclusion, missing and fractured teeth, orofacial trauma, and orofacial malignancies [ 11 , 13 , 18 , 19 , 20 , 21 ]. A study among newly-arrived refugees in Massachusetts indicated that oral diseases were the most common complaint in children and the second most common in adults [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), oral disease burdens are one of the leading health problems that refugees experience [ 17 ]. Among refugees, there is a high prevalence of major oral diseases such as dental caries, periodontal disease, malocclusion, missing and fractured teeth, orofacial trauma, and orofacial malignancies [ 11 , 13 , 18 , 19 , 20 , 21 ]. A study among newly-arrived refugees in Massachusetts indicated that oral diseases were the most common complaint in children and the second most common in adults [ 22 ].…”
Section: Introductionmentioning
confidence: 99%